2011
DOI: 10.1042/cs20100597
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 polyunsaturated fatty acids augment the muscle protein anabolic response to hyperinsulinaemia–hyperaminoacidaemia in healthy young and middle-aged men and women

Abstract: Increased dietary long-chain n-3 polyunsaturated fatty acid (LCn-3PUFA) intake stimulates muscle protein anabolism in individuals who experience muscle loss due to aging or cancer cachexia. However, it is not known whether LCn-3PUFA elicit similar anabolic effects in healthy individuals. To answer this question we evaluated the effect of 8 weeks of LCn-3PUFA supplementation (4 g·d−1 of Lovaza®) in nine 25–45 y old healthy subjects on the rate of muscle protein synthesis (by using stable isotope labelled tracer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
301
10
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(367 citation statements)
references
References 62 publications
18
301
10
7
Order By: Relevance
“…Aas et al (1) also observed an increase in basal glucose and fatty acid uptake after treatment with EPA in human skeletal muscle cells. This observation could probably be explained in terms of a general anabolic effect of -3 PUFAs, in line with results reported by Smith et al (43) showing increased muscle protein concentration in response to dietary intake of -3 PUFAs. However, in light of the observation that EPA or DHA did not increase p70 S6K phosphorylation, the activity of the anabolic master regulator mTOR appears not to be altered by these -3 PUFAs.…”
Section: Discussionsupporting
confidence: 90%
“…Aas et al (1) also observed an increase in basal glucose and fatty acid uptake after treatment with EPA in human skeletal muscle cells. This observation could probably be explained in terms of a general anabolic effect of -3 PUFAs, in line with results reported by Smith et al (43) showing increased muscle protein concentration in response to dietary intake of -3 PUFAs. However, in light of the observation that EPA or DHA did not increase p70 S6K phosphorylation, the activity of the anabolic master regulator mTOR appears not to be altered by these -3 PUFAs.…”
Section: Discussionsupporting
confidence: 90%
“…In our data, it is confusing that mTOR is more elevated in fat-1 sham mice that wt sham mice, unlike being decreased in fat-1 IRI mice than wt IRI mice. However, omega 3 intake increased mTOR-p70s6k signaling which control muscle protein anabolism and muscle protein growth in human [41]. It may be possible that omega 3 elevate mTOR in basal status kidney, like muscle.…”
Section: Discussionmentioning
confidence: 99%
“…During physiologic assessment, protein synthesis is not expected to increase in a fasting state. Studies have shown that v-3 supplementation improves skeletal muscle protein synthesis during a hyperinsulinemic-hyperaminoacidemic clamp where patients are in an anabolic state as opposed to under fasting conditions (4,5). Since there is a physiologic balance between protein synthesis and protein breakdown designed to compensate for each other to maintain a net nitrogen balance, our results are physiologically appropriate in that fish oil did decrease steady-state protein breakdown, which was in turn compensated for by a decrease in protein synthesis resulting in no appreciable change in net balance.…”
Section: Discussionmentioning
confidence: 99%